2(x-2)-3(4x-1)=0

Simple and best practice solution for 2(x-2)-3(4x-1)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x-2)-3(4x-1)=0 equation:


Simplifying
2(x + -2) + -3(4x + -1) = 0

Reorder the terms:
2(-2 + x) + -3(4x + -1) = 0
(-2 * 2 + x * 2) + -3(4x + -1) = 0
(-4 + 2x) + -3(4x + -1) = 0

Reorder the terms:
-4 + 2x + -3(-1 + 4x) = 0
-4 + 2x + (-1 * -3 + 4x * -3) = 0
-4 + 2x + (3 + -12x) = 0

Reorder the terms:
-4 + 3 + 2x + -12x = 0

Combine like terms: -4 + 3 = -1
-1 + 2x + -12x = 0

Combine like terms: 2x + -12x = -10x
-1 + -10x = 0

Solving
-1 + -10x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + 1 + -10x = 0 + 1

Combine like terms: -1 + 1 = 0
0 + -10x = 0 + 1
-10x = 0 + 1

Combine like terms: 0 + 1 = 1
-10x = 1

Divide each side by '-10'.
x = -0.1

Simplifying
x = -0.1

See similar equations:

| -(3x-5y+3)= | | 2.00+35*.30=x | | 9y^2-169x^2= | | 4=w-6 | | f(x)=3x-20 | | 5c^3+20c^2-105c=0 | | -3x-y=9 | | 8y+17=3y-3 | | 4x-3(x-1)=9x+15-7x | | 2r^2+r-15=0 | | (0.4x)-(2x)-(.8)=1.4 | | 9(d+8)= | | 2(3x+2)=6x+5 | | f(x)=4x-8 | | 5(d-5)+6= | | n=0.08*7496+7400 | | 6x+9y=15 | | 2(3x+2)=6x+2 | | 2.00+x*.30=12.50 | | 14=2+x | | 2(x-5)+7=8x | | 2b-6-11b-5= | | -3(t-2)+6t=7t-4 | | (5-6m)/m^2-9 | | 9(x+5)=8(x-6)+x | | f(16)=4x-8 | | 4(X+7)=2 | | 14a+16a= | | 9(x-5)=8(x-6)-x | | n^2-2-12=0 | | 5(2+x)+3x=-2(x+5) | | -3(-x+2)=2x-4 |

Equations solver categories